Sinergi Manajemen Organisasi dan Nilai Tafsir Q.S. Ash-Shaff: 4 dalam Membangun Tim Dakwah yang Solid dan Efektif di Era Digital - Moh. Bahrudin; Anwar Mukti; Agung Mandiro Cahyono; M. Luqman Hakim; Ahmad Nur Fathoni; Muhammad Burhanudin Nur Karim (North Press, 2024)
The digital era presents significant challenges for da'wah organizations, including team disintegration, ineffective communication, and burnout due to unstructured management. Addressing these issues requires a synergy between contemporary organizational management and Qur'anic values, particularly the metaphor of a